ANALISIS PENGARUH PENGUMUMAN BOND RATING TERHADAP RETURN SAHAM PERUSAHAAN DI BURSA EFEK JAKARTA PERIODE 2012-2014 - Noviantoro, Rinto (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2017)
Rinto Noviantoro: The purpose of this study to examine the impact of the announcement of bond rating on stock returns prior (the announcement of bond rating), stock return on day (bond rating announcement). Data used are daily stock return by Jakarta Stock Exchange (JSE), bond rating announcement by PT. PEFINDO, and firm are listing in Jakarta Stock Ekchange between 2012 to 2014. This research using 29 emitens as the sample bosed on purposive sampling. This data are analyzed with paired sample t-test and Oneway ANOVA.The analysis indicates that : (1) the defference are not significant between stock return an day bond rating announcement with before day bond rating announcement, (2) the difference are not significant between stock return on day bond rating announcement with after day bond rating announcement, (3) the difference are significant between stock return before bond rating announcement with after bond announcement (4) avarage stock return on day, before and after bond rating announcement are not significant differences.Key words: Obligasi, Return Saham